Are organic films from atmospheric aerosol and sea water inert to oxidation by ozone at the air-water interface?. (July 2017) - Jones, Stephanie H.; King, Martin D.; Ward, Andrew D.; Rennie, Adrian R.; Jones, Alex C.; Arnold, Thomas
Abstract: The heterogeneous oxidation of thin films of organic material extracted from real aerosol and sea-water samples was studied at the air-water interface using X-ray reflectivity. Oxidation of thin films of organic material extracted from real aerosol and sea-water is important in further understanding the impact of coated aerosols on the climate of the Earth. Surface active insoluble organic material extracted from the atmosphere was found to form stable films at the air-water interface (thickness measured as 10–14 nm). On exposure of the films to gas-phase ozone, no reaction (or change in the relative scattering length of the interface) was observed, indicating a potential lack of unsaturated organic material in the samples. Gas chromatography and electrospray ionization mass spectrometry showed the presence of saturated compounds in the samples. It is therefore proposed that the amount of unsaturated compounds as compared to saturated compounds in the atmospheric material is so low that the mass spectrometry analyses, as well as gas-phase oxidation are dominated by saturated material. A reaction was observed on exposure of the same films to aqueous phase hydroxyl and nitrate radicals and a film thinning mechanism is proposed to explain the change in scattering length of the film at the air-water interface. It can be suggested tentatively that oxidation by gas-phase ozone is not important in the atmosphere for organic films on aqueous atmospheric aerosol and that further studies should focus on radical induced oxidation of saturated organic material instead of unsaturated proxies that are typically studied. Graphical abstract: Highlights: Insoluble material extracted from atmospheric aerosol formed stable organic films at the air-water interface. The film material does not react with ozone but does react with the aqueous hydroxyl radical. Film material collected from filter with denuders to remove ambient ozone during sampling did not react with ozone. Insoluble material extracted from seawater formed stable organic film at the air-water interface and did not react with ozone. X-ray reflectivityhas been shown to be a new tool to study the oxidation of material in core-shell aerosol.